Design of LAPAN-A2 Satellite Telemetry Data Information System Using SDLC - Herawan, Agus; Rachim, Elvira; Sutjipto, Suci Sri Utami (Universitas Nusantara PGRI Kediri, 2022)
After several years of launch, the LAPAN-A2 satellite has produced a huge amount of telemetry data consisting of information on the status of the satellite's condition during orbit. The telemetry generated by the satellite is in the form of real-time telemetry and long-time telemetry. So far, telemetry data is only stored in a folder with a unique name. This method tends to be manual and makes it easier for users to analyze satellite conditions. This system was developed using the System Development Life Cycle (SDLC) approach, wherein the development process has five stages, namely planning, analysis, design, implementation, and testing. This paper will describe the design of a web-based satellite telemetry information system. The system has been tested using structural, functional, and usability tests. The evaluation results show that this information system is affordable and accepted well. The usability test results show that the LAPAN-A2 satellite, telemetry data information system, has met usability needs very well. Respondents have successfully carried out many experiments. In this case, operators and satellite analysis, with a question value of 86.22%, can be answered and 13.77% unable to be answered.